Surgical Management of Lagophthalmos with Gold Pessary - María Guadalupe Nieblas Serrano; Rogelio Rodríguez Cárdenas; Juan Jesús Ortega Landeros; Lucero Ramirez Mejia; Jesús Alejandro Olvera Rodríguez; Alvaro Sebastian Gutierrez Macklis; Alfonso Sandoval Polito; Alberto Jaramillo Sastré; Wendy Melisa Gomez Aragón; Andrés Eduardo Martínez López; Luis Fernando Castillo Cesareo; Angeles Anahi Mendoza Rojas; et al. (International Journal of Medical Science and Clinical Research Studies, 2025)
Gold weight implantation is a widely used surgical technique for managing lagophthalmos caused by facial nerve paralysis. This procedure involves placing a gold weight in the upper eyelid to facilitate passive closure, thereby protecting the cornea from exposure-related complications such as keratitis and ulceration. Advancements in implant design, such as elliptical shapes with suture holes for enhanced fixation, have reduced complications like migration, extrusion, and infection. Techniques including retrograde implantation and supratarsal fixation further improve placement accuracy and reduce postoperative morbidity. Despite its efficacy, long-term complications such as implant migration, cosmetic concerns, ptosis, and infection may arise, highlighting the importance of careful surgical planning and patient-specific approaches. Adjunctive measures, such as fascia lata grafts, have been shown to improve implant stability and minimize the need for revision surgeries. Gold weight implantation remains a reliable and effective solution for restoring eyelid function in patients with facial nerve paralysis, with continued refinements in techniques and materials contributing to enhanced functional and aesthetic outcomes.